Childhood Overweight, Social Media, and Osteoarthritis: Is there a Possible Emergent, yet Unrecognized Linkage? - Ray, Marks (International Journal of Eating and Weight Disorders, 2020)
Background Osteoarthritis, a serious and increasingly prevalent disabling global health condition found largely among older adults, has been linked to the presence of excess body weight. But what contributes to this growing health epidemic of excess weight, which is increasingly observed in children? Moreover, can a case be made for predicting a possible negative linkage between the pervasive use of social media from the earliest point in time and possible subsequent childhood overweight or obesity and late life osteoarthritis that may be amenable to intervention? Methods To examine the most probable answers to these questions, the EBSCO, Scopus and PUBMED data bases were sourced for relevant data. The extracted data were carefully reviewed, categorized and documented in narrative format. Results While one cannot readily carry out research to answer the above questions, prevailing data imply that there is more risk of being overweight in childhood, as well as acquiring possible later life disabling osteoarthritis, or a more serious manifestation of this disease, through the prolonged, unfettered and frequent use of social media in early and middle childhood. Conclusion Those in the realm of developing preventive strategies against childhood overweight or obesity as well as osteoarthritis are strongly encouraged to examine the role of the media environment and messages children are exposed early on in this regard. Alternately, children who already have disabilities, joint pain due to arthritis or other health conditions, and who may have to rely more on social media than others who are active- may suffer more readily from an energy imbalance and become overweight if due precautions against this are not taken.
Keywords: Childhood Overweight; Obesity; Osteoarthritis; Prevention; Social Media